A metabolomic study of the urine of rats with Alzheimer's disease and the efficacy of Ding‐Zhi‐Xiao‐Wan on the afflicted rats. Issue 8 (26th February 2020) - He, Yang; Wang, Yimin; Liu, Shu; Pi, Zifeng; Liu, Zhiqiang; Xing, Junpeng; Zhou, Hui
Abstract: As a well‐known traditional Chinese medicine formula, Ding‐Zhi‐Xiao‐Wan has long been used for the routine treatment of Alzheimer's disease. However, the mechanism of Ding‐Zhi‐Xiao‐Wan in treating Alzheimer's disease is unclear. Therefore, a nontargeted metabolomics method based on ultrahigh performance liquid chromatography with quadrupole time‐of‐flight mass spectrometry has been established to explore the metabolic variations in the urine of Alzheimer's disease rats and investigate the therapeutic mechanism of Ding‐Zhi‐Xiao‐Wan on Alzheimer's disease. To develop a better rat model of Alzheimer's disease, amyloid β25‐35 was injected into the bilateral hippocampus of Sprague–Dawley rats. Multivariate analysis approaches were applied to differentiate the urine components between the four groups. Thereafter, a targeted metabolomics method was used to verify the identified endogenous metabolites and determine the mechanism of action of Ding‐Zhi‐Xiao‐Wan. Altogether, 26 potential biomarkers were found, of which 15 biomarkers (10 of which are potential biomarkers found in nontargeted metabolomics) were identified. The results show that Ding‐Zhi‐Xiao‐Wan mainly affects the pathways of taurine and hypotaurine metabolism, tryptophan metabolism, and phenylalanine metabolism. Ding‐Zhi‐Xiao‐Wan might play a role in the treatment of Alzheimer's disease by mediating antioxidative stress, regulation of energy metabolism, improvement of intestinal microbes, and protection of nerve cells.